1982
DOI: 10.1111/j.1365-2230.1982.tb02483.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma zinc-serum albumin correlation: relevance to assessment of zinc status in humans

Abstract: Summary Plasma zinc and serum albumin were measured in an ostensibly healthy group of volunteers. Calculation of the correlation coefficient showed a small but significant correlation between plasma zinc and serum albumin in the total group studied (r= 0·35, P<0·05), The results indicate that in healthy individuals there is a small but significant correlation between serum filbumin and plasma zinc, but the low degree of correlation would suggest that there are other variables affecting plasma zinc in health. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1983
1983
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 33 publications
1
0
0
Order By: Relevance
“…This relationship suggests that a relative reduction in zinc concentration will also lower down the serum albumen concentration. Other studies have also reported a significant correlation between serum zinc and albumin, and a decline in the albumin concentration resulting in the decline of zinc as well [36,37]. Our study is in line with previous studies and it indicates that zinc is involved in the metabolism of proteins [38].…”
Section: Figure 3 Correlations Between Thyroid Hormones Iron and Ferritin (A) Tsh And Ferritin (B) Ft4 And Ferritin (C) Iron And Ft4 And supporting
confidence: 93%
“…This relationship suggests that a relative reduction in zinc concentration will also lower down the serum albumen concentration. Other studies have also reported a significant correlation between serum zinc and albumin, and a decline in the albumin concentration resulting in the decline of zinc as well [36,37]. Our study is in line with previous studies and it indicates that zinc is involved in the metabolism of proteins [38].…”
Section: Figure 3 Correlations Between Thyroid Hormones Iron and Ferritin (A) Tsh And Ferritin (B) Ft4 And Ferritin (C) Iron And Ft4 And supporting
confidence: 93%